A better way: New Zealand Association of Scientists 1992–2016 - Gregory, Geoff (New Zealand Science Review, 2016)
... the effectiveness of the policy/funder/provider separation principle is now in question and the efficacy of information sharing and joint policy development of these parties is in doubt. From: ‘There is a better way’, 2005 [1]. At the turn of the 1980s in the wake of the 1979 energy crisis, most of the developed world had suffered economic recession, which was then aggravated by the 1987 stock market crash. As part of the general economic stringency controls that ensued, governments of most OECD countries increasingly involved themselves in determining scientific research priorities in terms of value for the investment of taxpayers’ money. The UK, for example, having accepted Lord Rothschild’s 1972 proposal of applying the customer/contractor principle to government-funded science [2], required government-funded scientists to justify their work in terms of economic and social benefits for the nation. Under Margaret Thatcher’s premiership, in 1987, the separate centralised overseeing organisations, ACOST (Advisory Council on Science and Technology), which would control and direct research funds and priorities, and CEST (Centre for Exploitation of Science and Technology), which would identify priorities [3], were formed, and government research institutes were restructured and in several cases amalgamated or closed. The main criteria for research funding became selectivity and exploitability [4].